Mastering Blockchain : a technical reference guide to the inner workings of blockchain, from cryptography to DeFi and NFTs - Bashir, Imran, ....- (Birmingham : Packt Publishing, 2023)
Although this book covers the basics, including blockchain's technical underpinnings, cryptography, and consensus protocols, it doesn't shy away form advanced topics and practical expertise, such as decentralized application (DApp) development using smart contracts. Throughout the book, you'll explore blockchain solutions beyond cryptocurrencies, such as the Internet of Things (IoT) with blockchain, enterprise blockchains, and tokenization, and gain insight into the future scope of this fascinating and disruptive technology. By the end of this blockchain book, you will have gained a thorough understanding of the various facets of blockchain and understand the potential of this technology in diverse realworld scenarios.
Keywords: Blockchain